the Effect of Entrepreneur Characteristics, Social Support, Product Innovation on Development of Business in the DIY Giwangan Market - Saptaningsih Sumarmi (STKIP Singkawang, 2019)
This study aims to determine the influence of characteristic of entrepreneur, social support, product innovation, on the development of business traders in the DIY Giwangan Market. The respondents were traders in Giwangan market as many as 100 traders. Technique sampling used is stratified proportional random sampling. The methods of data analysis used is multiple regreession analysis. The results showed that the characteristic of entrepreneurship, product innovation partially does not affect the development of business. While social support is partially proven to influence business development. characteristic of entrepreneurship,social support, product innovation silmutanly affect the development of business.